Investigation of CsBr:BiBr3 precursor ratio concentration on cesium bismuth bromide perovskite formation - Low, Yiin Jian; Liew, Josephine Ying Chyi; Talib, Zainal Abidin; Lim, Hong Ngee; Kamarudin, Mazliana Ahmad; Choo, Thye Foo; Fen, Yap Wing; Lee, Han Kee; Salisu, Bashir; Shitu, Ibrahim Garba (Elsevier BV, 2023)
The effect of precursor ratios on the formation of Cs3Bi2Br9 via a re-precipitation synthesis method has been studied thoroughly. X-ray diffraction analysis showed that the precursor ratio was critical for the Cs3Bi2Br9 phase formation. The Cs-rich or Bi-rich precursor ratio resulted in diverse perovskite structure formation of Cs3BiBr6 and Cs3Bi2Br6 with micron size platelet and semi-micron size crystal morphology respectively. Unreacted BiBr3 precursor remains in the supernatant solution under Bi-rich conditions. The synthesized powder dispersed in toluene shows the degradation of the Cs3Bi2Br9 phase at Cs-rich conditions. Photoluminescence quantum yield (PLQY) of 0.73 % was identified in Cs3Bi2Br9 with a large contribution to the exciton-related recombination process. A precursor ratio CsBr:BiBr3 of 3.0:2.0 is proposed to form a single-phase Cs3Bi2Br9 structure, as the deviation in precursor ratio would promote the Cs3BiBr6 structure growth and affect the material’s optical performance.